How do I express cos3 theta in terms of sin theta?

So far I GOT

=cos (2 theta + theta)

=cos 2 theta cos theta - sin 2 theta sin theta

=((2(1-sin^2 theta))-1)cos theta - sin 2 theta sin theta

=((2-2sin^2 theta)-1)cos theta - sin 2 theta sin theta

Now..... how do I eliminate the cos theta in order for it to become all sin theta

And

How do I solve this sin5 theta

So far I GOT

=sin(2 theta + 3 theta)

=sin 2 theta cos 3 theta + cos 2 theta sin 3 theta

=(2sin theta cos theta)(4 cos^3 theta - cos theta)+(1-2sin^2 theta)(3sin theta-4ain^3theta)

I want to know how to express cos 3 theta in terms of sin theta in order for me to solve, I think, sin 5 by substitution theta.Please help me also how to simplify the expression sin 5 theta.

thanks

My edit: Added "by substitution"